2015
DOI: 10.9738/intsurg-d-14-00300.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Graft Selection Criteria in Living-Donor Liver Transplantation: The Jikei Experience

Abstract: In living-donor liver transplantation, graft selection is especially important for the safety of the live donor and an acceptable outcome for the recipient. The essential medical requirements for living liver donation at Jikei University Hospital are as follows: an adult aged 65 years or younger, in good general condition, with partial liver volume of more than 35% of the standard liver volume (SLV) for the recipient, and without severe liver steatosis. Based on our criteria, we performed 13 living-donor liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…This may explain the correlation between the length of ICU stay and the amount of ascites present. Although management regarding ICU stay may differ in each country, several Japanese studies reported similar lengths of ICU and hospital stays to this study [39,40]. It should be noted that other treatments, such as colloid and pressor administration, nutritional support, and antimicrobial agents against infection, should be conducted properly, in addition to a large of fluid resuscitation for perioperative management in liver transplantation.…”
Section: Discussionsupporting
confidence: 54%
“…This may explain the correlation between the length of ICU stay and the amount of ascites present. Although management regarding ICU stay may differ in each country, several Japanese studies reported similar lengths of ICU and hospital stays to this study [39,40]. It should be noted that other treatments, such as colloid and pressor administration, nutritional support, and antimicrobial agents against infection, should be conducted properly, in addition to a large of fluid resuscitation for perioperative management in liver transplantation.…”
Section: Discussionsupporting
confidence: 54%